Historical evolution of the Educational Inspection through the main legal references - Cáceres Reche, María Pilar; Hinojo Lucena, Francisco Javier; Aznar Díaz, Inmaculada (Avances en Supervisión Educativa, 2007)
Traditionally, the Educational Inspection has been included by laws; such as a function exclusively referred to control and supervision, representing the Government and, thus, it is a part of a higher hierarchical status, own a Public Authority.So, the inspection tasks were focused to others and different purposes in relation to the present, as well as, its main role was an authority characterized by a highly relation centralized and vertical respect to the school and the educational community.In this paper it is collected a review to the educational laws more important (L.G.E., LOGSE, LOPEGCE, LOCE, etc.) that they have made up a valuable contribution for the conceptual change and the development of inspection understood, now, in a function based on the support and advice to schools in a new framework of organizational culture (horizontal) through the consensus and negotiation.